UV light and abrasion’s role in degrading plasticulture films - Ana Carolina Cugler Moreira; Florian Wilken; Alessandro Fabrizi; Peter Fiener (PLoS ONE, 2026)
Plastic films play a crucial role in agriculture by enhancing growing conditions and protecting crops through various applications, such as mulch films or greenhouses. However, the degradation of plasticulture films may occur in the field, generating secondary microplastics and soil pollution. Investigating the degradation of agricultural plastic films in soil systems is essential for understanding their environmental abundance, and it is crucial for developing effective mitigation strategies to avoid potential harm to soil health and agricultural productivity. In this study, various low-density polyethylene (LDPE) films commonly used in plasticulture were exposed to different times of ultraviolet (UV) radiation and to mechanical abrasion. Subsequently, the samples were analysed to assess their chemical properties, wettability, surface roughness, and elasticity changes. Although the films did not exceed their manufacturer’s designated lifetime after the UV exposure time applied in this study, photodegradation and indications for the removal of microplastic surface particles through mechanical abrasion were observed even after short UV radiation exposure. Abrasion has been identified as an important modulator in photodegradation by removing UV radiation sheltering surface particles and thereby exposing undegraded film surfaces to UV radiation. However, changes in elasticity and susceptibility to fragmentation into macroplastic residues have not been identified.